Thermal Characterization of Buildings with as-is Thermal-Building Information Modelling - Víctor Pérez-Andreu; Antonio Adán Oliver; Carolina Aparicio-Fernández; José-Luis Vivancos Bono (Buildings, 2023)
Developing methodologies to accurately characterise the energy conditions of existing building stock is a fundamental aspect of energy consumption reduction strategies. To that end, a case study using a thermal information modelling method for existing buildings (as-is T-BIM) is reported. This proposed new method is based on the automatic processing of 3D thermal clouds of interior zones of a building that generates a semantic proprietary model that contains time series of surface temperatures assigned to its surface elements. The proprietary as-is T-BIM automatically generates an as-is BEM model with gbXML standards for energy simulation. This is a multi-zone energy model of the building. In addition, the surface temperature data series of the as-is T-BIM model elements permit the calculation of their thermal transmittances, increasing the calibration options of the obtained as-is BEM model. To test the as-is TBIM method, a case study compares the as-is BEM model obtained by as-is T-BIM methods with the one obtained by standard methods for the same building. The results demonstrate differences in geometry, transmittance, and infiltration values, as well as insignificant differences in annual air conditioning energy consumption or the comfort parameters tested. This seems to indicate shorter modelling times and greater accuracy of the as-is T-BIM model.